Management of trickle irrigation for banana: Hydrodynamic processes and sensor placement at the root zone - Edvaldo B. Santana Junior; Eugênio F. Coelho; Marcelo R. dos Santos; Alisson J. P. da Silva; João B. R. da S. Reis; Bruno L. da S. Pereira (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT Information on soil hydrodynamic processes assists in explaining the soil-water-plant relationship and has practical applications to irrigation management, such as the definition of soil water sensor placement. The objective of this study was to detail the hydrodynamic process in the soil root zone and to define the location for placement of soil water sensor under different configurations of trickle irrigation in banana crops. Three micro-sprinkler emitters with flow rates of 70 (T1), 53 (T2), 35 L h-1 (T3), and two drip system, one with one drip line per row of plants (T4), and another with two drip lines per row of plants (T5) were evaluated. The experiment was conducted in a randomized block design with five repetitions. Higher water extraction was found for irrigation systems with higher flow rates for all configurations of trickle irrigation systems. Soil moisture sensors in drip systems should be placed at distances of 0.75 to 0.81 m from the pseudo stem and at depths of 0.33 to 0.44 m. Under micro-sprinkler systems, soil water sensors should be placed at 0.75, 0.77 and 0.83 m from the pseudo stem towards to the emitter and at depths of 0.33, 0.48 and 0.55 m for emitter flow rates of 35, 53 and 70 L h-1, respectively.